Hydrodynamics of an OWC Device in Irregular Incident Waves Using RANS Model - Kshma Trivedi; Amya Ranjan Ray; Parothidil Anjusree Krishnan; Santanu Koley; Trilochan Sahoo (Fluids, 2023)
This research examines the hydrodynamic performance of an oscillating water column device placed over a sloping seabed under the influence of irregular incident waves. The numerical model is based on the Reynolds-veraged Navier–Stokes (RANS) equations with a modified <semantics>k−ω</semantics> turbulence model and uses the volume-of-fluid (VOF) approach to monitor the air–water interface. To explore the hydrodynamic performance of the OWC device in actual ocean conditions, the Pierson–Moskowitz (P-M) spectrum was used as the incident wave spectrum, together with the four distinct sea states which occur most often along the western coast of Portugal. The numerical simulation offers a comprehensive velocity vector and streamline profiles inside the OWC device’s chamber during an entire cycle of pressure fluctuation. In addition, the impact of the irregular wave conditions on the free-surface elevation at various places, the pressure drop between the chamber and the outside, and the airflow rate via the orifice per unit width of the OWC device are investigated in detail. The results demonstrate that the amplitudes of the inward and outward velocities via the orifice, free-surface elevations, and flow characteristics are greater for more significant wave heights. Further, it is noticed that the power generation and capture efficiency are higher for a seabed having moderate slopes.